RanBP2/Nup358 enhances miRNA activity by sumoylating Argonautes - Shen, Qingtang (PLoS Genet, 2021)
Mutations in RanBP2 (also known as Nup358), one of the main components of the cytoplasmic filaments of the nuclear pore complex, contribute to the overproduction of acute necrotizing encephalopathy (ANE1)-associated cytokines. Here we report that RanBP2 represses the translation of the interleukin 6 (IL6) mRNA, which encodes a cytokine that is aberrantly up-regulated in ANE1. Our data indicates that soon after its production, the IL6 messenger ribonucleoprotein (mRNP) recruits Argonautes bound to let-7 microRNA. After this mRNP is exported to the cytosol, RanBP2 sumoylates mRNP-associated Argonautes, thereby stabilizing them and enforcing mRNA silencing. Collectively, these results support a model whereby RanBP2 promotes an mRNP remodelling event that is critical for the miRNA-mediated suppression of clinically relevant mRNAs, such as IL6.